TRESK is a key regulator of nocturnal suprachiasmatic nucleus dynamics and light adaptive responses - Tatjana Lalic (Nature Portfolio, 2020)
The suprachiasmatic nucleus (SCN) ensures rhythmic electrical activity that varies between day and night to determine circadian behaviours. The authors show that TRESK channels provide a feedback mechanism to maintain the SCN in the appropriate state for nocturnal light-induced behavioural changes.